Visual analysis of the finite‐time lyapunov exponent - Sagristà Sellés, Antoni; Jordan, Stefan; Sadlo, Filip (Computer graphics forum, 2020)
In this paper, we present an integrated visual analytics approach to support the parametrization and exploration of flow visualization based on the finite‐time Lyapunov exponent.